2022
DOI: 10.1021/acs.est.1c07171
|View full text |Cite
|
Sign up to set email alerts
|

Source contributions and drivers of physiological and psychophysical cobenefits from major air pollution control actions in North China

Abstract: North China is among the most polluted regions in the country, and human exposure to PM2.5 (particulate matter with an aerodynamic diameter less than 2.5 μm) in this region has led to severe health consequences. The region has also benefited the most from emission reductions in recent years. It is of interest to understand to what extent and through which paths emissions from different sectors cause adverse health impacts. Here, we present the results of a full evaluation of the health benefits of emission con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(119 reference statements)
1
7
0
Order By: Relevance
“…At the same time, economically, lower PM 2.5 levels produced less social costs [ 31 ], effectively alleviating the inequality of health spending [ 32 ]. Other studies also confirmed the same results [ 17 , 18 , 19 ], which again validated the physical utility of stove renovation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…At the same time, economically, lower PM 2.5 levels produced less social costs [ 31 ], effectively alleviating the inequality of health spending [ 32 ]. Other studies also confirmed the same results [ 17 , 18 , 19 ], which again validated the physical utility of stove renovation.…”
Section: Discussionsupporting
confidence: 74%
“…As shown in Table 1 , previous studies have considered the impact of clean energy renovation on air quality, individual health and psychological well-being [ 11 , 17 , 18 , 19 , 20 ], while few studies have considered the impact of clean energy intervention on individuals’ perception and willingness to protect themselves. On the other hand, in many developing countries, such as India, it has been found that stove renovation projects were limited by local perceptions and economies [ 12 , 21 , 22 , 23 , 24 , 25 , 26 ], while the factors that influence the willingness to pay for stove renovation in rural China are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, indoor pollution was responsible for >70% of premature mortality in 2014 for rural residents in North China due to their considerable use of solid fuel for heating and cooking. 22 Hence, exploring the public health contributions of high PM 2.5 concentration range in both ambient and indoor environments is necessary for the development of effective mitigation policies. Herein, trends in severe hazy days (SHDs) and severe indoor pollution days (SIPDs) are examined, and the effects of mitigation policies (particularly CHC) are discussed, with a focus on severe haze in ambient air, and analogously, severe pollution in indoor air.…”
Section: ■ Introductionmentioning
confidence: 99%
“…47 Psychophysical Impact. A previously described 22 model calculating the subjective well-being (SWB) based on psychophysical experiments conducted in Beijing 48 was modified to define the integrated subjective well-being (ISWB), which addressed the psychophysical impact of ambient PM 2.5 concentrations in this study. The scores (0− 5) of four negative emotions, including worry, stress, depression, and irritation, were derived based on the modeled ambient PM 2.5 concentrations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A few studies have estimated the air pollutant emissions from residential solid fuel combustion at various spatial scales and showed that 21% of global PM 2.5 emissions were from residential coal and biomass combustion in 2010 . In China, residential combustion accounted for 21% of total SO 2 emissions and 27% of total PM 2.5 emissions in 2015, which are responsible for 58% of population-weighted health risk .…”
Section: Introductionmentioning
confidence: 99%